2016
DOI: 10.1016/j.bbr.2016.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Impaired cued and spatial learning performance and altered cannabinoid CB1 receptor functionality in the substantia nigra in a rat model of diabetic neuropathy

Abstract: Diabetes, and associated diabetic neuropathic pain, impact negatively on cognitive function. However, the underlying mechanisms remain poorly understood. This study investigated neuropathic pain-related behaviour and cognitive function in the rat streptozotocin (STZ) model of diabetes, and assessed cannabinoid1 (CB1) receptor functionality in discrete brain regions. Male Lister-Hooded rats received STZ (60 mg/kgs.c.) or vehicle. Sensory responses were assessed in von Frey and Hargreaves tests. Cognitive, motor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Moreover Zoja et al observed that in kidney biopsies from patients with diabetic nephropathy, CB2 is down-regulated, and moreover, its deletion worsens the kidney state, confirming the receptor protective action [129]. Moriarty et al observed that STZ-diabetic rats show an alteration in CB1 receptor functionality in the substantia nigra, which may be associated with diabetes and diabetic neuropathic pain [133]. Surely all of this evidence needs further investigation, but new perspectives for the management of this complex degenerative disease are surely emerging.…”
Section: The Ec System In Type 1 Diabetes Mellitusmentioning
confidence: 99%
“…Moreover Zoja et al observed that in kidney biopsies from patients with diabetic nephropathy, CB2 is down-regulated, and moreover, its deletion worsens the kidney state, confirming the receptor protective action [129]. Moriarty et al observed that STZ-diabetic rats show an alteration in CB1 receptor functionality in the substantia nigra, which may be associated with diabetes and diabetic neuropathic pain [133]. Surely all of this evidence needs further investigation, but new perspectives for the management of this complex degenerative disease are surely emerging.…”
Section: The Ec System In Type 1 Diabetes Mellitusmentioning
confidence: 99%
“…The duration of diabetes mellitus is thought to be one of the key factors for rodent studies on DNP and its effective treatment (Obrosova 2009 ), as well as diabetes-related cognitive deficits (Biessels and Gispen 2005 ). This is due to the fact that both these diabetes-related complications share a common etiology, i.e., neuropathy (Moriarty et al 2016 ). Since the main objective of the present research was to assess the impact of pregabalin on learning and memory in conditions related to DNP, this study was performed 3 weeks after STZ injection.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the cognitive abilities of STZ-treated diabetic rodents are based on several learning tasks (Biessels et al 2002 ; Moriarty et al 2016 ). To assess the effect of pregabalin on learning and memory in diabetic mice, we used a passive avoidance task.…”
Section: Discussionmentioning
confidence: 99%
“…The novel object recognition test is designed to evaluate deficits in recognition memory in rodents, as a measure of the severity of the brain injury. The procedure used for the novelobject recognition test was similar to that described previously (26,27), with some modifications. The apparatus consisted of a Perspex arena (45 cm 2 ).…”
Section: Behavioral Testingmentioning
confidence: 99%